2009
DOI: 10.1099/mic.0.021501-0
|View full text |Cite
|
Sign up to set email alerts
|

Is gas-discharge plasma a new solution to the old problem of biofilm inactivation?

Abstract: Conventional disinfection and sterilization methods are often ineffective with biofilms, which are ubiquitous, hard-to-destroy microbial communities embedded in a matrix mostly composed of exopolysaccharides. The use of gas-discharge plasmas represents an alternative method, since plasmas contain a mixture of charged particles, chemically reactive species and UV radiation, whose decontamination potential for free-living, planktonic micro-organisms is well established. In this study, biofilms were produced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
81
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 57 publications
12
81
0
Order By: Relevance
“…Giaouris et al [33] reported that traditional vortexing with beads did not completely remove biofilm cells from the substrate. Microscopic techniques, including scanning electron microscopy [34] and epifluorescence microscopy [35,36], are not suitable for quantitative enumeration of biofilms.…”
Section: Disinfection Efficacy Of Hssp Against E Coli Biofilm Estimmentioning
confidence: 99%
“…Giaouris et al [33] reported that traditional vortexing with beads did not completely remove biofilm cells from the substrate. Microscopic techniques, including scanning electron microscopy [34] and epifluorescence microscopy [35,36], are not suitable for quantitative enumeration of biofilms.…”
Section: Disinfection Efficacy Of Hssp Against E Coli Biofilm Estimmentioning
confidence: 99%
“…Sterilization is also demonstrated by an understanding of the natural bioburden (numbers and types of viable microorganisms) present on/in the product to be sterilized; this is indeed the real target for sterilization. When the bioburden is low, the sterilization challenge is not great, but when it is high and associated with significant clumping (such as observed with viruses and various types of bacteria, including the presence of biofilm) (26), this provides a significant challenge to the sterilization process. However, in many cases these vegetative bacterial cells (27) and other microorganisms are generally much less resistant to gas plasmas (20) (Fig.…”
Section: Log Of Cfu Exposure Time (Min)mentioning
confidence: 99%
“…Giaouris et al (2005) reported that traditional vortexing with beads did not completely remove biofilm cells from the substrate. Microscopic techniques, including scanning electron microscopy (Jones and Bradshaw, 1996) and epifluorescence microscopy (Joaquin et al, 2009;Rossoni and Gaylarde, 2000), are not suitable for quantitative enumeration of biofilms. Conductometric assays allow the detection of biofilm bacteria without disrupting the biofilm structure, because these assays detect the presence of biofilms via the metabolic activity of attached cells.…”
Section: Resultsmentioning
confidence: 99%